TRADITIONAL MEDICINE PLANTS OF WAAI VILLAGE COMMUNITIES, MALUKU PROVINCE - Daro, Prichilia; Hiariej, Adriana; Nindatu, Maria (RUMPHIUS, 2020)
This study aims to determine the types of plants used by the village community as traditional medicine and to find out how to use these types of medicinal plants. The research was conducted in Waai Village, Central Maluku District, Salahutu District. This research was conducted using survey methods and interviews with the community using a list of questions. The sampling technique was purposive sampling, the sample was determined as much as 15% of the total village population in Waai which consisted of 1500 heads of families and as many as 225 respondents were designated as heads of families. The results showed that there were 71 species of medicinal plants from 45 families. The most used plant parts are leaves, whole plants, fruit, roots, stems, rhizomes and tubers. Medicinal plants are generally used by the village community to cure ailments, aches and pains and to increase milk production. The utilization process is simple, by boiling, smoking, squeezing, rubbing and grating.